Effect of night and day on preterm infants in a newborn nursery: randomised trial. Issue 6557 (15th November 1986) - Mann, N P; Haddow, R; Stokes, L; Goodley, S; Rutter, N
Abstract : The effect of alternating night and day on sleep, feeding, and weight gain in 41 healthy preterm infants was examined in a randomised controlled trial. Twenty infants from a night and day nursery, where the intensity of light and noise was reduced between 7 pm and 7 am, spent longer sleeping and less time feeding and gained more weight than 21 infants from a control nursery, where the intensity of light and noise was not reduced. Differences were significant and became apparent only after discharge home; they were still present three months after the expected date of delivery, when infants from the night and day nursery were an average of 0.5 kg heavier (p less than 0.02). These findings suggest that physical environment has an effect (either direct or indirect) on the subsequent behaviour of preterm infants and that exposure to night and day is beneficial.